A rare case of infliximab induced myeloperoxidase-cytoplasmic antineutrophil cytoplasmic autoantibody positive cutaneous vasculitis - Robinson, Carly J.; Jairath, Neil K.; Davis, Jon C.; Yang, Hongyu H. (International Journal of Research in Dermatology, 2022)
Drug-induced cutaneous vasculitis is a known autoimmune complication of tumor necrosis factor (TNF) inhibitors with many instances resulting in the production of newly formed antibodies. We report a 21-year-old female with a past medical history of Crohn’s disease controlled with infliximab who presented to dermatology with a purpuric rash and crusted plaques of her distal lower extremities. Biopsy of a lesion revealed perivascular lymphocytes, neutrophils and eosinophils, vessel wall damage, and dermal eosinophils consistent with a drug-induced vasculitis. Follow up labs assessing for antibodies revealed unusual findings of an elevated cytoplasmic-antineutrophil cytoplasmic autoantibody (C-ANCA) titer and myeloperoxidase (MPO) antibody level making this patient MPO-C-ANCA positive. The patient’s lesions were treated with both oral and topical steroids, colchicine, and transition of her infliximab to ustekinumab with subsequent improvement of her lesions and normalization of antibody titers.